Ag120-Mediated Inhibition of ASCT2-Dependent Glutamine Transport has an Anti-Tumor Effect on Colorectal Cancer Cells - Yu, Wei; Huang, Jianwen; Dong, Qichao; Li, Wenting; Jiang, Lei; Zhang, Qian; Sun, Li; Yuan, Shengtao; He, Xu (Frontiers in Pharmacology, 2022)
Metabolic reprogramming is considered to be a hallmark of cancer, and increased glutamine metabolism plays an important role in the progression of many tumors, including colorectal cancer (CRC). Targeting of glutamine uptake via the transporter protein ASCT2/SLC1A5 (solute carrier family 1 member 5) is considered to be an effective strategy for the treatment of malignant tumors. Here, we demonstrate that Ag120 (ivosidenib), a mutant isocitrate dehydrogenase 1 (IDH1) inhibitor approved for the treatment of certain cancers, acts as an ASCT2 inhibitor in CRC cells. Ag120 blocked glutamine uptake and metabolism, leading to reduced cell proliferation, elevated autophagy, and increased oxidative stress in CRC cells in vitro and in vivo, potentially via the ERK and mTOR signaling pathways. These effects occurred independently of mutant IDH1 activity and were supported by experiments with ASCT2-depleted or -overexpressing cells. These data identify a novel mechanism of Ag120 anti-tumor activity and support further exploration of ASCT2 inhibitors for cancer therapy.